The impact of a patient web communication intervention on reaching treatment suggested guidelines for chronic diseases: A randomized controlled trial. Issue 11 (November 2017) - Glaser, Emma; Richard, Claude; Lussier, Marie-Thérèse
Highlights: This study included multi-morbid adult chronic disease patients who did not meet treatment targets. Completing a web communication intervention increased likelihood of reaching treatment goals. Changes in blood pressure, glycated hemoglobin and lipid profiles resembled differences seen in self-management studies. Abstract: Objective: Examine the impact of a PACE (Prepare, Ask, Check, Express) inspired web-based communication intervention alone or combined with a workshop on reaching treatment goals for patients suffering from chronic diseases (CDs), compared to usual care. Methods: Three arm single-blind RCT in community primary care (PC) practices. PC practitioners ( n  = 18) had a CD patient caseload, and practicing >5 years. Patients >40 years old, English speaking, computer literate, not reaching treatment goals for hypertension, type II diabetes, and/or dyslipidemia. Interventions: (1) web-intervention and (2) web intervention and nurse facilitated workshop and (3) usual care. Outcome: Proportion of patients meeting all treatment suggested guidelines for the diagnoses they were enrolled for. Results: Patients ( n  = 322) were randomized, and of these 221 returned for follow up. Patients in the web group were 1.42 times more likely to meet targets compared to usual care [95% CI: 1.00–2.00], a statistical difference not seen in the combined group. Sensitivity analyses were performed to mitigate bias due to loss to follow up. Conclusions: Training patients in communication skills using a website positively affects reaching treatment goals for hypertensive, diabetic and dyslipidemic patients. Practice implications: Web communication interventions are an effective tool that can be used in primary care.